BRIDGING THE EPISTEMOLOGICAL DIVIDE: ARSYAD AL-BANJARI'S MA'RIFAH AS A RESPONSE TO WESTERN EPISTEMOLOGICAL DILEMMAS - Ihsan, Nur Hadi; Azam Mohd Amin , Wan Mohd; Tsaqib , Muhammad Ammar; Jusmidar, Jusmidar (Al-Qalam, 2025)
Western epistemology encounters significant challenges due to its secular and materialistic orientation, which restricts the sources of knowledge to sensory perception and empirical experimentation. This study analyzes Muhammad Arsyad al-Banjari’s concept of ma‘rifah as an epistemological alternative to these dilemmas. Adopting a qualitative, library-based method, the research applies Miles, Huberman, and Saldaña’s analytical model, framed within an integration of Islamic epistemological principles and comparative philosophical analysis. The primary source is Kanz al-Ma‘rifah by al-Banjari, supported by cross-referenced verification. The findings indicate that, according to al-Banjari, ma‘rifah is attainable through three key paths: Nūr Muhammad, mutu qabla an tamūtu, and fanā’. This concept provides an epistemological paradigm that integrates physical and metaphysical dimensions of knowledge, reconciles rational and intuitive methodologies, and transcends the subject-object dichotomy through spiritual experience. Through the ‘irfānī method focusing on purification of the heart and spiritual discipline, ma‘rifah offers a comprehensive epistemology that refines rational and sensory faculties, thereby presenting a critical alternative to the empiricism that dominates Western epistemology.